Social Movements and their Demands toward the Constitutent Assembly in Bolivia and Ecuador - Fernández, Blanca S. (2012)
This article is a comparative analysis of the Confederation of Indigenous Peoples of Eastern Bolivia (CIDOB, as per the Spanish acronym) and the Confederation of Indigenous Nationalities of the Ecuadorian Amazon (CONFENIAE, as per the Spanish acronym). The analysis takes into account the characteristics of the territories where these organizations unfold, the time-period during which they emerged (the eighties), as well as the political and institutional transformations they have brought about in both countries. The article also analyzes the organizations’ actions and demands surrounding land disputes and reforms. This analysis is based on the period between 1990 and 2007, during which land issues became more visible and were finally translated into both countries’ constitutions.